Clinical utility of cerebrospinal fluid biomarkers measured by LUMIPULSE® system. Issue 12 (2nd November 2022) - Nojima, Hisashi; Ito, Satoshi; Kushida, Akira; Abe, Aki; Motsuchi, Wataru; Verbel, David; Vandijck, Manu; Jannes, Geert; Vandenbroucke, Ina; Aoyagi, Katsumi
Abstract: Objectives: Cerebrospinal fluid (CSF) biomarkers of Alzheimer's disease (AD) are well‐established in research settings, but their use in routine clinical practice remains a largely unexploited potential. Here, we examined the relationship between CSF biomarkers, measured by a fully automated immunoassay platform, and brain β‐amyloid (Aβ) deposition status confirmed by amyloid positron emission tomography (PET). Methods: One hundred ninety‐nine CSF samples from clinically diagnosed AD patients enrolled in a clinical study and who underwent amyloid PET were used for the measurement of CSF biomarkers Aβ 1–40 (Aβ40), Aβ 1–42 (Aβ42), total tau (t‐Tau), and phosphorylated tau‐181 (p‐Tau181) using the LUMIPULSE system. These biomarkers and their combinations were compared to amyloid PET classification (negative or positive) using visual read assessments. Several combinations were also analyzed with a multivariable logistic regression model. Results: Aβ42, t‐Tau, and p‐Tau181, and the ratios of Aβ42 with other biomarkers had a good diagnostic agreement with amyloid PET imaging. The multivariable logistic regression analysis showed that amyloid PET status was associated with Aβ40 and Aβ42, but other factors, such as MMSE, sex, t‐Tau, and p‐Tau181, did not significantly add information to the model. Conclusions: CSF biomarkers measured with the LUMIPULSE system showed good agreement with amyloid PET imaging. The ratio of Aβ42 with the other analyzed biomarkers showed a higher correlation with amyloid PET than Aβ42 alone, suggesting that the combinations of biomarkers could be useful in the diagnostic assessment in clinical research and potentially in routine clinical practice.